THE ASSOCIATION OF URINARY SPECIFIC GRAVITY AND ACIDITY WITH UROLITHIASIS - Agung Nugroho, Raden Fenditya; Hendri, Ahmad Zulfan; Ali, Zulfikar (Indonesian Urological Association, 2020)
Objective: This study aimed to know the association between urinary specific gravity and acidity with the formation of urolithiasis. Material & Methods: This retrospective descriptive study was conducted among proven urolithiasis patients reporting to the Kardinah Hospital, Tegal. The patient’s age, gender, anatomical sites of the stone, and biochemical parameters were obtained from the case records. The correlation of kidneys stone with specific gravity and pH changed according to anatomical sites of stone was analyzed by One way Anova. Results: The resulted show urinary stones patients with lower pH tend to have a higher probability of stone formation but not specific to its location. Higher pH values were found in the patient with urinary stones at the kidney, ureter, and also bladder. The average of specific gravity in ureter stone patients was lower than stones on other sites. One-way ANOVA shows no statistically significant difference in patient's urinary pH with stones on different sites, but there is a statistically significant difference in specific gravity examination (p<0.05) on ureter stone patients compared to other locations. There is a statistically significant difference (p=0.000) of urine specific gravity of ureter stone compared to other anatomical sites with the lower mean value. Conclusion: A decrease in urinary pH is associated with the risk of urinary stone formation. The specific gravity value of the patient’s urine with kidney and bladder stones is higher than the patient with ureter stones but there is no association of urine specific gravity toward the risk of urinary stone formation.